Identification and purification of transferrin- and lactoferrin-binding proteins of Bordetella pertussis and Bordetella bronchiseptica. - Menozzi, F D (1991)
Bordetella pertussis and Bordetella bronchiseptica were both able to grow in iron-deficient medium when supplemented with iron-saturated human lactoferrin or transferrin but not with human apotransferrin. Direct contact between the transferrins and the Bordetella cells did not appear to be required for growth but considerably improved the growth of the organisms. Analysis of B. pertussis and B. bronchiseptica whole-cell lysates from cultures carried out in iron-deficient or iron-replete media revealed iron-repressible proteins (IRPs) of 27 kDa in B. pertussis and of 30, 32, 73.5, and 79.5 kDa in B. bronchiseptica. Iron-inducible proteins of 16, 23.5, 36.5, and 92.5 kDa and of 17, 23.5, 70, 84, and 91 kDa were also identified in B. pertussis and B. bronchiseptica, respectively. By use of affinity chromatography with iron-saturated human lactoferrin or transferrin as ligands, the 27- and 32-kDa IRPs from B. pertussis and B. bronchiseptica, respectively, were specifically isolated. By using iron-chelated affinity columns, we showed that these proteins exhibit an affinity for iron. Cell fractionation experiments indicated that both of these proteins are probably associated with the outer membrane. Growth of the organisms under modulating conditions showed that the production of these IRPs is not under the genetic transcriptional control of vir or bvg, the general virulence regulon in Bordetella spp.